Effect of Potentiostatic and Galvanostatic Electrodeposition Modes on the Basic Parameters of Solar Cells Based on Cu2O Thin Films. (1st January 2016) - Abdelfatah, Mahmoud; Ledig, Johannes; El-Shaer, Abdelhamid; Sharafeev, Azat; Lemmens, Peter; Mosaad, Mohsen Mohamed; Waag, Andreas; Bakin, Andrey
Abstract : We present here a direct comparison of potentiostatic and galvanostatic modes of Cu2 O thin films electrodeposition for the manufacturing of solar cells keeping all other steps identical. The ZnO:Al window layers were deposited using sputtering. The solar cells were characterized by scanning electron microscopy and Raman spectroscopy that show pyramidal shape and phonon modes for Cu2 O thin films, respectively. Current – voltage (J-V), capacitance – frequency (C–f) and the external quantum efficiency (EQE) measurements were performed to understand the heterojunction properties. The results show that there is no big difference in V oc values comparing devices manufactured by the potentiostatic and the galvanostatic mode. While the J sc values for the case of potentiostatic growth mode are higher compared to the galvanostatic one even for the same thin film thickness, this difference can be attributed to the textured top surface morphology of the devices and the minority carrier diffusion length ( L diff ) as concluded from SEM and EQE measurements. For solar cells grown by the galvanostatic mode with Cu2 O thin film thickness increasing from 1 to 2.3 μm the efficiency increases by around 19.3%, while it increases by around 27.7% for devices grown by the potentiostatic mode. Overall, devices grown by a potentiostatic mode have higher efficiency than those from a galvanostatic mode.